2016
DOI: 10.3329/jafmc.v12i1.39966
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality Outcome in Late Preterm Neonates at a Tertiary Care Hospital

Abstract: Introduction: The morbidity and mortality in late preterm neonates is higher than term neonates. The main reason is the relative physical and neurologic immaturity, though there is no significant difference in the weight or the size of the two groups. Objective: The study was conducted to compare the early neonatal morbidity and mortality (within first 7 days of life) in late preterm infants (34–36 6/7 weeks) with those in term neonates (37–41 6/7 weeks). Materials and Methods: This was a prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…The ndings indicate that nearly a quarter (23.8%) of preterm infants and only 4.1% of term infants died during the neonatal period. A similar mortality rate of 28% for preterm and 6% for term infants was reported in a study conducted in Bangladesh 11 . Contrary, a lower mortality rate among preterm infants was reported in high-income countries like Australia (7.7%) and the USA (1.4%) 12,13 .…”
Section: Discussionsupporting
confidence: 84%
“…The ndings indicate that nearly a quarter (23.8%) of preterm infants and only 4.1% of term infants died during the neonatal period. A similar mortality rate of 28% for preterm and 6% for term infants was reported in a study conducted in Bangladesh 11 . Contrary, a lower mortality rate among preterm infants was reported in high-income countries like Australia (7.7%) and the USA (1.4%) 12,13 .…”
Section: Discussionsupporting
confidence: 84%
“…This may be due to the fact that KMC service facilitates skin-to-skin contact, optimal breastfeeding, and prevention of apnea and colonization of the neonate's skin with mutualistic maternal skin microbial flora. These clinical significances of KMC help prevent the neonates from being hypothermia, hypoglycemic, distressed, and developing infection thereby increasing their survival ( 33 , 35 , 45 , 49 , 50 ). Therefore, preterm infants whose birth weight is <2,000 g and have relatively stable vital signs should always receive KMC service to optimize their survival.…”
Section: Discussionmentioning
confidence: 99%
“…The present study shows that the proportion of preterm infants with neonatal morbidity was nearly twice that of term infants (84.9% vs. 43.3%). In a study conducted in Bangladesh, similar proportions were observed, whereby 76% of preterm and 28% of term infants had morbidities 11 . The most common morbidities among preterm infants were RDS (75.2%) and apnea (72.3%).…”
Section: Baseline Neonatal Characteristics Are Presented In Tablementioning
confidence: 62%
“…The risk of overall morbidity was also higher in preterm infants than term infants by seven-folds. infants was reported in a study conducted in Bangladesh 11 . Contrary, a lower mortality rate among preterm infants was reported in high-income countries like Australia (7.7%) and the USA (1.4%) 12,13 .…”
Section: Baseline Neonatal Characteristics Are Presented In Tablementioning
confidence: 86%